Middle triassic dry-land phases in southern Slovenia - Dozet, Stevo (Materiali in tehnologije, 2010)
In the Middle Triassic lithostratigraphic sequence of southern Slovenia and neighbouring Gorski Kotar, Croatia, three dry-land phases have been recognized: 1 - between the Lower and Middle Triassic, 2 - in between the Anisian stratigraphic sequence, and 3 - between the Anisian and Ladinian beds. Traces of the Anisian volcanism have also been discovered. The dry-land episodes of the non-deposition and volcanic activity are ascribed to synsedimentary tectonic movements of the Alpine tectonic cycle. However, new data enable a new approach to the paleogeographical evolution of the area. In the Triassic "Dolomite" Complex, lenses of kaolinite deposits occur, representing an important correlation horizon for the basal Ladinian beds. They consist chiefly of kaolinite and quartz admixed in smaller quantities by hematite, goethite, nontronite, gibbsite, groutite and montmorillonite. The kaolinite deposits were formed in a marsh with weathering of the pyroclastic materials.
Keywords: karbonatne kamnine; vulkanske kamnine; kaolinit; elektronska mikroskopija; EDS analiza; XRD; srednji trias; Dinaridi; Slovenia; Slovenija